APPLICATION OF SOCIONICS METHODS FOR COMPLETING - Харченко, В.; Шмельова, Т.; Сікірда, Ю.; Землянський, А. (Proceedings of National Aviation University (archive), 2012)
Joint activity plays an important role in the work of aviation professionals, but now in Ukraine sociometric and socionics approaches to acquisition of flight crews and controllers’ teams are not used. With the system approach personality types of aviation professionals and their interactions during the performance of professional tasks in the small group on the example of the controllers’ team were identified. The experiment allowed to receive sociometric and socionic indicators of the air traffic controllers, to conduct correlation analysis of these parameters and to determine the closeness of links between the levels of individual’s interactions. The practical value of research consists on developing of automated module for determining the operator’s socionic characteristics and for evaluation of the effectiveness of their interactions during the air traffic controlling, in particular, in flight emergences.